The Influence of Leadership and Communication of Srikandi Celebes Agency Leaders on the Level of Life Insurance Sales in Makassar City - Aris, Hardiyanti; Yusmanizar, Yusmanizar; Fitriana, Fitriana (Journal of Management and Administration Provision, 2023)
Leadership and communication are the most fundamental aspects in an organization, especially in a marketing team that requires coordination from various parties towards the same goal. This research focuses on the influence of leadership and communication from the leader of Srikandi Celebes Agency on the level of life insurance sales in Makassar City. This research method employs a quantitative approach by collecting data through questionnaires, consisting of 45 statements distributed to agents of Srikandi Celebes Agency in Makassar City. The sample size used in this research is 38 agents, selected using a census technique. Multiple linear regression analysis is utilized to measure the relationship between leadership and communication variables of the leader and the level of life insurance sales. The research results indicate that effective leadership and communication from the leader of Srikandi Celebes Agency significantly influence the level of life insurance sales in Makassar City. The coefficient of determination (R2) is 0.977 or 97.7%, indicating a strong relationship between the independent variables, leadership (X1) and communication (X2), and the dependent variable, sales level (Y). This suggests a close relationship between the variables. Based on the collaborative research conducted, there is a significant influence of leadership (X=) and communication (X2) on sales level (Y).